Implementación y desarrollo de una herramienta de evaluación de guías rápidas, instructivos de fallas y capacitación de equipos en el hospital san Ignacio - Casas Perez, Jessica Yurley (Escuela Colombiana de Ingeniería Julio Garavito, 2020)
The San Ignacio University Hospital is an institution with a long history in the health sector, it was founded in 1942 in order to generate a field of training, practices and research for the Faculty of Medicine of the Javeriana University, with a social purpose, to be able to welcome the population of scarce resources and with it, to generate the opportunity to cover the health needs of the country, with ethical, human and social commitment. The institution is going to implement a project that aims to provide a sufficient consultation tool to access information easily and effectively, generating immediate solutions, improving response time and optimizing resources, conserving useful life of the equipment, improving the techniques of use and proper handling of the equipment by the healthcare personnel, in addition, having the digitization of the necessary documentation for each equipment, making the information easy and accessible to all the personnel of the Hospital that requires it.
Keywords: Salud; Capacitaciones; Health; Trainings